TINJAUAN YURIDIS TERHADAP HAK-HAK PEJALAN KAKI DI KOTA SAMARINDA BERDASARKAN UNDANG- UNDANG NOMOR 22 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN JALAN - Lingai, Irenius (Journal of Law ( Jurnal Ilmu Hukum ), 2018)
ABSTRACTIRENIUS LINGAI, 2019. â€œJuridical Review of Pedestrian Rights in Samarinda City Based on Law Number 22 Year 2009 concerning Road Traffic and Transportationâ€. Advisor I, Dr. Irman Syahriar S.H., M.Hum and Advisor II Ms. Khairunisah S.H., M.Hum.Traffic or passing vehicles and people on the road occurs because of the process of moving people from one place to another, traffic problems arise when the number of vehicles does not match the capacity of the road. When the vehicle does not reach the appropriate speed, at that time there is a violation of pedestrian rights.The purpose of this study is to be able to know the legal rules relating to pedestrian rights in Samarinda, to know the sanctions that can be imposed on violators of pedestrian rights, and to know how the role of the Samarinda city government in fulfilling pedestrian rights .In this paper the author uses this type of research with a normative juridical approach method where legal research is carried out by examining library materials or secondary data as basic material to be investigated by conducting a search of the regulations and the literature relating to the problems studied.The results of the study indicate that the legal arrangements relating to pedestrian rights have been regulated in Law No. 22 of 2009 concerning Road Traffic and Transportation where this legal arrangement includes the prohibition on the use of sidewalks by road users other than pedestrians, that motorists must prioritize pedestrians, and rules related to the role of the government in the implementation of pedestrian facilities. Sanctions that can be imposed on violators of pedestrian rights in the form of criminal sanctions and can also be carried out ticket to offenders. There are 3 agencies that have a role related to pedestrian rights, namely the Department of Transportation of Samarinda City, the Civil Service Police Unit and the Department of Public Works of Samarinda City in the field of Highways.Keywords: Pedestrian Rights